Emerging Equity Market Comovements: Trends and Macroeconomic Fundamentals - Eiling, Esther; Gerard, Bruno (Review of Finance, 2015)
Abstract Emerging equity markets have become increasingly interrelated over the past two decades. For a sample of thirty-two emerging markets from four different regions, we find significant positive time trends in cross-country correlations within regions, correlations across regions, and in comovements with the rest of the world. Furthermore, we examine the economic mechanisms that drive these trends. We find that official market liberalization, a continuous measure of equity market openness, equity market development, and to some extent, trade openness all play a role. However, we show important heterogeneity across regions, both in the speed at which comovements increase over time and in the underlying macroeconomic channels.